Evaluation of red cell indices and manual reticulocyte parameters in iron deficiency, vitamin B12 deficiency and beta thalassemia minor patients in a tertiary care hospital - Shamsuddin, Shabeera; Upadhyaya, Krishnaraj; Sudhakar, Shubha; Z., Aejaz Ahamed (International Journal of Research in Medical Sciences, 2022)
Background: Reticulocytes are the youngest erythrocytes released from the bone marrow. Their increase or decrease can be an indicator of erythropoietic activity or failure. Manual reticulocyte count is an assay traditionally used to evaluate the status of erythropoiesis. Reticulocyte parameters could be cost effective methods to guide the clinician in treating anaemias. Aim of current study was to evaluate the role of routine red blood cell parameters and reticulocyte parameters in differentiating various anaemias. Methods: This retrospective cross-sectional study was conducted by retrieving the laboratory parameters of patients admitted at Yenepoya medical college hospital from January 2021 to July 2021, duration of 6 months. Fifty cases of anaemia were included. These included records of patients with anaemia based on Serum Ferritin levels, Vitamin B12 levels, and beta thalassemia cases confirmed using electrophoresis. Other various parameters like mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration were also taken into consideration for descriptive statistics. Results: Statistically significant correlation was observed for reticulocyte count, reticulocyte production index and other red blood cell parameters like MCV, MCH and MCHC between iron and vitamin B12 deficiency anaemias. No statistically significant correlation was observed in the beta thalassemia group but specifically showed significance in MCV. Conclusions: Reticulocyte count and reticulocyte production index and good markers apart from the routinely used traditional red blood cell parameters in differentiating between iron deficiency and vitamin B12 deficiency anaemias. However, in beta thalassemia minor cases, the mean corpuscular volume is a better marker. Present study showed male gender predominance in anemia which could be due to ethnic and topographical variations